Study of Interaction of Mercuric Chloride with Bovine Serum Albumin by Multi-Spectroscopic Method - Shen, F.; He, Y.-M.; Zhou, Y. (Asian Journal of Chemistry, 2013)
The interaction of mercuric chloride with bovine serum albumins was investigated under the simulative physiological conditions. The fluorescence spectra in combination with UV absorption and circular dichroism spectra were used in the present work. A strong fluorescence quenching reaction of mercuric chloride towards bovine serum albumin was observed and the quenching mechanism was regarded as static quenching procedure. The association constant (K) at different temperatures as well as thermodynamic parameters e.g., enthalpy change (DH), entropy change (DS) and Gibb's free energy (DG), were calculated. The results showed that the hydrophobic force plays an important role in the interaction of mercuric chloride to bovine serum albumin. In addition, the result of synchronous fluorescence showed that binding site of mercuric chloride is nearer to tryptophan than that of the tyrosine residue, alteration of secondary structure of bovine serum albumin in the presence of mercuric chloride was evaluated using the data obtained from UV and circular dichroism spectroscopies.